The impact of energy poverty on the health and welfare of the middle-aged and older adults - Wang, Yibo; Wu, You; Wang, Chenyu; Li, Li; Lei, Yalin; Wu, Sanmang; Qu, Zhi (Frontiers in Public Health, 2024)
Drawing upon data from the 2018 CHARLS , this paper utilizes MEPI and a 10% threshold indicator to respectively assess the energy poverty (EP) status among middle-aged and elderly populations in China, focusing on the unavailability and unaffordability of energy services. Additionally, a econometric model is constructed to investigate the effects of EP on the health and welfare of middle-aged and elderly populations. Regression results indicate that EP exerts a significant negative impact on the health and welfare of middle-aged and elderly populations. This conclusion remains robust after conducting endogeneity and robustness tests, demonstrating its validity. Finally, based on the calculation results, we propose relevant policy recommendations including enhancing energy services for elderly households in rural areas, integrating household energy alternatives with targeted poverty alleviation, enhancing monitoring mechanisms, and conducting energy education activities to alleviate EP and improve the quality of life of middle-aged and elderly people.